Northern extension of Lesueurigobius friesii (Malm, 1874) (Pisces: Gobiidae) distribution and the gobiid diversity decline along the Norwegian coast - Kovačić, Marcelo; Svensen, Rudolf (2019)
Lesueurigobius friesii was collected in Eidsfjorden, Sognefjorden, Norway, extending its known distribution range north as the new northernmost locality of this species. Globally, the northernmost presence of gobies is along the coast of Norway. Their diversity along the Norwegian coast showed an evident latitude gradient of gobiid diversity with a clear decrease from south to north. The significant regression structural change was found at the 63/64° N latitude band followed by a 36.4% decrease in gobiid species diversity. The species traits of gobiids north of the regression breaking point and those restricted to the south of it were compared. The only significantly more frequent characteristic of species passing north of the regression breaking point is the large depth range that reach down to the shelf break. All species present north of the point, except Thorogobius ephippiatus (that barely passes it) belong to Oxudercinae (i.e. to Pomatoschistuslineage of that subfamily).
Glavoč repaš Lesueurigobius friesii sakupljen je u Eidsfjorden, Sognefjorden, Norveška, što predstavlja najsjeverniji nalaz ove vrste. Globalno, najsjevernija rasprostranjenost glavoča nalazi se uz obale Norveške. Raznolikosti vrsta glavoča jasno se smanjuje od juga prema sjeveru uzduž Norveške obale. Statistički značajna strukturna promjena regresije utvrđena je na pojasu 63/64° sjeverne zemljopisne širne popraćena 36.4% smanjenjem raznolikosti vrsta glavoča. Osobine vrsta glavoča sjeverno od točke loma regresije uspoređene su s osobinama vrsta ograničenim južno od nje. Jedina značajno češća osobina vrste glavoča koje prolaze sjeverno od točke loma regresija je veći raspon dubina, koji kod ovih vrsta seže do ruba kontinentske podine. Također sve vrste sjeverno od točke loma, osim vrste Thorogobius ephippiatus (koja je jedva prolazi), pripadaju potporodici Oxudercinae, točnije Pomatoschistus grupi te potporodice.
Bibliografija: str. 153-155.
Summary ; Sažetak.
Keywords: Gobiidae -- Glavoč repaš -- Rasprostranjenost -- Raznolikost vrsta; Norveška